COVID-19 among pregnant women: management outcome and risk of transmission to newborns in western India - Monga, Anuradha; Sardana, Shikha; Sen, Sangeeta; Rani, Babita; Archunan, Priya; Khoiwal, Susheela (International Journal Of Community Medicine And Public Health, 2021)
Background: The WHO declared a global pandemic of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 in March 2020. With so much female population in reproductive period in India the effect of corona virus in pregnancy warrants attention as the impact of maternal infection during pregnancy in India remains poorly understood. Objectives of current study were to know the management outcome and risk of transmission among COVI-19 positive pregnant women admitted in a tertiary care institute in western India. Materials: The present cross sectional study was conducted among 217 admitted COVID-19 positive pregnant women in a tertiary care institute in western India from May 2020 to April 2021. Data were collected from the department of obstetrics and gynaecology after taking permission from the head of department of obstetrics and gynaecology. Results: Most of patients were asymptomatic and managed conservatively but some also needed special interventions. Out of 217 patients 124 patients delivered in the hospital, 5 maternal deaths, one stillbirth and one congenital anomaly was reported. Only 25% of patients had normal delivery rest had caesarean and one neonate was found COVID-19 positive. Around one forth deliveries were pre term. Conclusions: The study suggests that most women do not have severe illness and that transmission of infection to infants of infected mothers is uncommon but there are increased chances of pre-term delivery. Majority of the women and neonates were managed and discharged without any major complications. But in some cases COVID in pregnancy may complicate the situation; so it should be handled by a multidisciplinary team of experts in COVID-19.